Katolicisme i Ingemanns danmarkshistorie: En større fortælling om Nord og Syd - Martinsen, Lone Kølle (Dansk Teologisk Tidsskrift, 2022)
This study presents a reading of Catholicism in the historical novels of the Danish author Bernhard Severin Ingemann, written between 1824 and 1836, in the light of the so-called Nordic Sonderweg. The idea of a Nordic Sonderweg has been propounded in historical studies since the early 1990s and has gained significance ever since. The main idea is that the notion of a free peasant class, combined with Lutheranism, played a crucial role in the rise of modern democratic societies. Nordic peasants – so it is argued – enjoyed more freedom and equality, were more trusting, and earned greater respect and prestige than their fellows in southern European countries, who were hampered by feudalism, coercion, and Catholicism. My main argument is that Ingemann, as a pastoral enlightener in the North, represents the idea of a Nordic Sonderweg in his novels too and that his conception of Catholicism can be understood in the light of this grand narrative.